Impact of Networks and Social Capital on Organisational Learning: A Study on Weihai Economic and Technological Development Zone in China - Hong, Jee Young (2005)
This report aims to study the extent of networks and the impact of social capital on organisational learning. Organisational learning is highly linked to creating, acquiring, and transferring knowledge that is considered as a crucial source of lasting competitive advantage and improving organisational performance in the complex business world of the 21st century. Learning involves individuals and their activities, behavioural and emotional activities that are also an important aspect of network and social capital. Therefore, understanding of the relationship between organisational learning, networks and social capital helps an organisation to develop effective organisational learning.